CD83+ B cells alleviate uveitis through inhibiting DCs by sCD83 - Feng, Meng; Wang, Xin; Zhou, Shuping; Li, Minghao; Liu, Tingting; Wei, Xunbin; Lin, Wei (Immunology, 2023)
Soluble CD83 (sCD83) exerts immunosuppressive functions in many autoimmune diseases, including experimental autoimmune uveitis (EAU), but the cells and mechanisms involved are unclear. This study showed that CD83+ B cells were the main sources of sCD83. They alleviated the symptoms of EAU and decreased the percentage of T cells and DCs in the eyes and lymph nodes. These CD83+ B cells decreased IL‐1β, IL‐18 and IFN‐γ secretion by DCs through sCD83. sCD83 interacted with GTPase Ras‐related protein (Rab1a) in DCs to promote Rab1a accumulation in autolysosomes and inhibit mTORC1 phosphorylation and NLRP3 expression. Hence, CD83+ B cells play a regulatory role in EAU by secreting sCD83. The lack of regulation of CD83+ B cells might be an important factor leading to hyperimmune activation in patients with autoimmune uveitis. CD83+ B cells suppress activated DCs in uveitis, indicating the potential therapeutic role of CD83+ B cells in uveitis. Meng et al. reports that CD83+B cell inhibit the metabolism and the secretion of IL‐18 and IL‐1β in DCs by promoting Rab1a to degrade and decrease the expression of mTORC1 and NLRP3 in experimental autoimmune uveitis. Then, the inhibition of sCD83 on DCs further suppresses the activation and IFN‐γ secretion in T cells. These negative regulatory effectors prevent IFN‐γ+ T cells from damaging eye tissue.